A refined medium to enhance the antimicrobial activity of postbiotic produced by Lactiplantibacillus plantarum RS5 - Ooi, May Foong; Foo, Hooi Ling; Loh, Teck Chwen; Mohamad, Rosfarizan; Abdul Rahim, Raha; Ariff, Arbakariya (Nature Research, 2021)
Postbiotic RS5, produced by Lactiplantibacillus plantarum RS5, has been identified as a promising alternative feed supplement for various livestock. This study aimed to lower the production cost by enhancing the antimicrobial activity of the postbiotic RS5 by improving the culture density of L. plantarum RS5 and reducing the cost of growth medium. A combination of conventional and statistical-based approaches (Fractional Factorial Design and Central Composite Design of Response Surface Methodology) was employed to develop a refined medium for the enhancement of the antimicrobial activity of postbiotic RS5. A refined medium containing 20 g/L of glucose, 27.84 g/L of yeast extract, 5.75 g/L of sodium acetate, 1.12 g/L of Tween 80 and 0.05 g/L of manganese sulphate enhanced the antimicrobial activity of postbiotic RS5 by 108%. The cost of the production medium was reduced by 85% as compared to the commercially available de Man, Rogosa and Sharpe medium that is typically used for Lactobacillus cultivation. Hence, the refined medium has made the postbiotic RS5 more feasible and cost-effective to be adopted as a feed supplement for various livestock industries.